Evaluation of the impact of social aid on development in Sub-Saharan African countries (1994-2010) - JORI, Daniel (KDI School, 2016)
This thesis evaluated the impact of social aid on national development of Sub-Saharan African countries and give policy recommendations on the kinds of aid that donors should provide much in order to stimulate development in those countries. The study used a data covering a panel of 40 countries in the region over the period between 1994 and 2010. The study finds that social aid had a significant effect on long term development in the Sub Saharan African region. This effect was possibly by the lasting effect of social services such as education and health in people’s productivity. The results however, have failed to prove that social aid only works where domestic policies are good. However, this finding maybe a result of the bias data and the narrowness of the policy index and should not be relied on. The analysis has strengthened an argument made by Reddy and Minou (2009) that social aid is more useful in promoting long term national development. However, there is no strong evidence that social aid has positive impact on HDI and it is difficult to say that social aid is more effective than infrastructure aid.
Thesis(Master) --KDI School:Master of Public Policy,2016